Immune thrombocytopenia – what are the new treatment options?. (September 2013) - Hallam, Simon; Provan, Drew; Newland, Adrian C
Abstract : Introduction: Primary immune thrombocytopenia (ITP) is a minor disease for many patients; however, the natural history is variable and unpredictable. Many patients who are in otherwise good health can be left untreated, especially if their platelet counts are close to 20 × 10 9 /l. The overall mortality rate for ITP is < 1%, and the morbidity and mortality associated with treatment can be worse than the disease. Areas covered: ITP is not purely due to platelet destruction and in a significant proportion platelet production is sub-optimal; the review will cover the newer developments with the thrombopoietin receptor agonists (TPOrAs) of which two agents, romiplostim and eltrombopag, are now licensed and these will be placed in context to conventional treatment. Expert opinion: There is an increasing understanding of the natural history of ITP and an increasing evidence-based approach to the disease and its management. Treatment should be aimed at the patient with a bleeding risk and should minimise the risk of adverse effects while maximising the chances of response. Few, if any, treatments are curative and treatment strategies need to be designed in ITP that manage patients with what can be a life-long condition with periodic relapses.